It’s All Eve’s Fault: The Evolution of a Written and Visual Interpretive Tradition - Englard, Yaffa (Religion and the arts, 2022)
The traditional reading of the biblical account of the Garden of Eden has left a weighty imprint on Western civilization, holding Eve solely to blame for introducing sin into the human world and thus the loss of Paradise, suffering, and death. This paper seeks to demonstrate the way in which Jewish and Christian theological and interpretative traditions of this story are concretely exemplified in medieval visual representations whose influence can still be seen in the twenty-first century.